Intron Retention as a Mode for RNA-Seq Data Analysis - Zheng, Jian-Tao; Lin, Cui-Xiang; Fang, Zhao-Yu; Li, Hong-Dong (Frontiers in Genetics, 2020)
Intron retention (IR) is an alternative splicing (AS) mode that introns, rather than being spliced out as usual, are retained in mature mRNAs. It was previously considered as the consequence of mis-splicing and received very limited attention in the past. Only until recently, IR has become a mode of interest for transcriptomic data analysis for its recognized roles in gene expression regulation and associations with complex diseases. In this work, we first discussed the function of IR in regulating gene expression in a number of biological processes such as neuron differentiation and activation of CD4+ T cells. Next we briefly reviewed its association with diseases such as Alzheimer’s disease (AD) and cancers. Then, we described the state-of-the-art methods for IR detection including IRFinder and iREAD, with their principles pinpointed and their advantages and limitations discussed. Finally, we discussed the challenges for IR detection and potential ways through which IR detection methods could be improved.